Procedure of Circumstantial Evidences in Islamic Criminal Law - Mushtaq Aḥmad; Muhammad Zakariya; al Azhari, Zia Ullah (Journal of Islamic and Religious Studies, 2019)
Qara’in - usually translated as circumstantial evidence - is a derived form of Arabic word " " قر ن which literally means a fact associated or accompanied with an event or circumstances. But when an event or circumstances discloses such associated or accompanied fact then such a fact becomes circumstantial evidence. Both proto-juristic and modern legal terms held circumstantial evidence for an evidence which is offered to prove certain attendant circumstances from which the existence of the fact at issue may be inferred. In Islamic Law, majority of jurists do not endorse Qara’in as an authoritative evidence, particularly, in offences leading to corporal punishments. On the other side, Ibn Farhun from Malikites and Ibn Qayyem from Hanbalites terms it equal to the direct evidence of Iqrar and Shahadah. It is not very strange that Dr. Anwarullah, a prominent Muslim scholar and Prof. Robert Preach are of the opinion that circumstantial evidence is, after all, more authentic even than the aforesaid two evidences. Herbert Broom- a western legal expert- also says that certain hidden facts can be deducted from the mode of a relevant act or to some extent it is modus operandi which gives birth to a circumstantial evidence. In this shortened article the juristic opinion of some early and contemporary legal experts has been discussed as to judge the legal mode and authenticity of circumstantial evidence.